Evaluation of the formalin-Tween concentration technique for parasitic detection - Methanitikorn R. (2014)
The formalin-Tween sedimentation method was compared with the formalin-ether sedimentation for parasitic detection. Of a total 297 fecal specimens examined, 72.1% were positive. The formalin-tween technique was effective for ascertaining helminths, particularly Ascaris lumbricoides, Trichuris trichiura and hookworm eggs; however it has less capability for protozoa detection. This method is simple, inexpensive, less time consuming and highly sensitive when detecting the parasitic infection, particularly when focusing on helminth eggs.